Tropical Bubbles : Asset Prices in Latin America, 1980-2001 - Herrera, Santiago (World Bank, Washington, DC, 2014)
The authors test for the existence of asset price bubbles in Latin America in 1980-2001, focusing mainly on stock prices. Based on unit root and cointegration tests, they find that they cannot reject the hypothesis of bubbles. They arrive at the same conclusion using Froot and Obstfeld's intrinsic bubbles model. To examine empirical regularities of these bubble episodes in the region, the authors identify periods of significant stock price overvaluation. They quantify the relative importance of different factors that determine the probability of bubble occurrence, focusing on the contrast between the country-specific variables and the common external factors. They include as country-specific variables both the level and the volatility of domestic credit growth, the volatility of asset returns, the capital flows to each country, and the terms of trade. As common external variables, they consider the degree of asset overvaluation in the U.S. stock and real estate markets and the term spread of U.S. Treasury securities. To quantitatively assess the relative importance of each factor, they estimate a logit model for a panel of five Latin American countries from 1985 to 2001. In general, the authors find that the marginal probabilities of common and country-specific variables are of roughly the same order of magnitude. This finding contrasts with those of previous studies that real asset returns in Latin America are dominated by local factors. Finally, the authors explore the main channels through which asset prices affect real economic activity, with the most important being the balance sheet effect and its impact on bank lending. They show how the allocation of bank lending across different sectors responded sensitively to real estate prices during the boom years in countries that experienced banking crises. Thus asset price bubbles have long-lasting effects in the financial sector and, through this channel, on growth. Another channel through which asset prices-particularly stock market prices-affect long-run growth is through their effect on investment. The authors find a strong positive association between stock prices and investment and a negative effect of stock price volatility on investment. An additional motive for the central bank to monitor asset prices is the general coincidence of the crash episodes identified by the authors with currency crises in the region in the past two decades.